Systematic Review Approach to identifying key trends in adaptation governance at the supranational level - Bizikova, L.; Echeverría, D.; Hammill, A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
In this paper authors have analyzed peer-reviewed literature on adaptation governance focused on food security at the supranational level. A total of 281 papers were collected, of which 52 met our focus. We used 10 criteria (and 74 sub-criteria) to categorize the included papers. With research presented in these papers as our focus, we looked at key aspects of food security explored, identified types of governance measures and major challenges, and finally developed an understanding of the location of the research teams and involved countries. Overall, we found that the supranational focus in the context of adaptation governance on food security is not prevalent in current peer-reviewed literature—only approximately 16 per cent of the papers focus on this topic. In terms of the identified trends, there was a strong focus on developed countries and research led by teams from these countries; the governance systems aimed to prepare for a range of climate change impacts; and finally, there was limited interest in exploring the role of regional agencies in adaptation governance. In terms of future research needs, there is a strong need to develop processes for the integration of diverse sectors and issues when designing policies on food security in the context of climate change. It is also important to improve the skills and opportunities of research teams in the Global South to engage effectively in research on food security and governance.